Edition konsequent Nr. 45c. Reprint aus: AIZ Nr. 45, 1933. "Der Richter, der Gerichtete" - Heartfield, John (1933)
Edition konsequent Nr. 45c. Reprint aus: AIZ Nr. 45, 1933. "Der Richter, der Gerichtete".